Wound‐related complications and clinical outcomes following open globe injury repair. (19th June 2015) - Kong, George YX; Henderson, Robert H; Sandhu, Sukhpal S; Essex, Rohan W; Allen, Penelope J; Campbell, William G
Abstract Background Careful surgical management of traumatic wounds is important in open globe injury repair. This study examines the clinical outcomes following repair of open globe injuries with particular focus on wound‐related issues. Design Retrospective, cohort study of consecutive open globe injuries presenting to a tertiary referral eye hospital from 1 January 2009 to 31 December 2011. Participants A total of 267 eyes of 263 patients, mainly male (82.5%) with a mean age of 44.8 (range: 4–97) years. Average follow up was 6.9 months. Methods All cases classified according to Ocular Trauma Classification Group. Main Outcome Measures Visual outcomes, risk factors for and rates of postoperative complications and endophthalmitis. Results There were 83 globe ruptures, 182 penetrating and 2 perforating eye injuries, of which 43 cases had intraocular foreign body. Factors contributing to final visual acuity (VA) <6/60 were poor presenting VA (odds ratio [OR] = 16.0, 95% confidence interval [CI]: 4.81–53.1), globe rupture (OR = 4.64, [1.99–10.8]), retinal detachment (OR = 3.40, [1.19–9.74]) and age ≥50 (OR = 2.45, [1.05–5.74]). Wound leak occurred in 44 eyes (16%). Of these, 18 (41%) proceeded to re‐suturing. Factors contributing to wound leak were stellate‐shaped wound (OR = 3.28, [1.39–7.73]) and delayed presentation (OR = 2.80, [1.02–7.71]). Ten eyes (3.7%) developed endophthalmitis. Factors associated with endophthalmitis were delayed presentation (OR = 8.91, [1.71–46.6]), microbial keratitis (OR = 12.5, [1.85–85.0]) and lens capsule breach (OR = 12.4, [1.85–83.1]). Conclusions Wound leak is an important postoperative complication of open globe injury repair. Delayed presentation is an important risk factor for postoperative wound leak and endophthalmitis. Prompt and meticulous wound management of open globe injury may reduce these complications.